2019
DOI: 10.1016/j.jastp.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of suborbital flight operation using PESTLE

Abstract: Suborbital flight has progressively emerged as the potential future transport trend, whether for space tourism or other applications. While several design concepts have been explored thus far for the suborbital flight operation, one of the main lingering concerns is actually the destination of the flight. The altitude of 100 km, which is the commonly chosen destination for suborbital flight, provides an imaginary separation between air and space. The quest for this separation sparks intense debates not only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…During the study, factors of key importance for the development of DWHR systems were identified. To this end, PESTLE analysis ( Figure 1) was used, which is classified as a foresight study, and enables a context to be formed for further studies [32]. PESTLE facilitates identification and classification of external factors impacting the study subject into political, economic, social, technological, legal, and environmental issues.…”
Section: Identification Of Key Factors Using Pestle Analysismentioning
confidence: 99%
“…During the study, factors of key importance for the development of DWHR systems were identified. To this end, PESTLE analysis ( Figure 1) was used, which is classified as a foresight study, and enables a context to be formed for further studies [32]. PESTLE facilitates identification and classification of external factors impacting the study subject into political, economic, social, technological, legal, and environmental issues.…”
Section: Identification Of Key Factors Using Pestle Analysismentioning
confidence: 99%
“…Eqs. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) have been applied. It can be seen that the ranking of alternatives is similar to those Table 8 shows the net outranking flows, the positive outranking flow φ þ a i ðÞ and the negative outranking flow φ À a i ðÞ .…”
Section: Application Of the Topsis Edas Moora Copras And Promethee Methodsmentioning
confidence: 99%
“…The weights of the criteria in these cases are not determined. The PESTLE analysis has been implemented to analyze of the suborbital flight operation [1]; to determine the weak signals classification to detect threats and opportunities from web [2]; to analyze the renewable energy sector environment [3]. The integration of PESTLE and SWOT analysis is presented in [4] to analyze the Renewable Energy for Island Countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, along with the shift from government-driven to market-driven drivers of space activities, commercial spaceflight has become an important driver of global space activities, and the commercialization of suborbital flight has developed rapidly [ 1 ]. Unlike civil aviation flight methods, the suborbital flight is a flight between both gravity and aerodynamics, as the speed of flight around the earth is not reached, the vehicle is equivalent to making a parabola back to earth in space [ 2 ]. Compared to a normal flight, the suborbital flight time will be shortened several times; compared to a spacecraft, suborbital vehicles are cheap and reusable, thus presenting a huge economic value [ 3 ].…”
Section: Introductionmentioning
confidence: 99%